أثر حجم العينة على مؤشرات الدلالات الإحصائية والعملية في رسائل الماجستير بالجامعات العمانية = The effect of sample size on statistical and practical significance levels used in master’s theses in Education at Omani Universities - AlWahaibi, Ibrahim Said Humaid; Al-Hidabi, Dawood Abdulmalek Yahya; AlKharusi, Hussain Ali Talib (IIUM Press, International Islamic University Malaysia, 2021)
هدفت الدراسة إلى بحث أثر حجم العينة على كل من مستويات الدلالة الإحصائية ومؤشرات الدلالة العلمية في الاختبارات الإحصائية المستخدمة في رسائل الماجستير التربوية المنجزة بالجامعات العمانية. وتم استخدام المنهج الوصفي المسحي للإجابة على أسئلة الدراسة. وتكونت عينة الدراسة من (628) رسالة ماجستير بنسبة (33.14%) من مجتمع الدراسة والذي بلغ (1895) رسالة ماجستير. وصمَّم الباحث أداة تحليل المحتوى لجمع البيانات الخاصة بالاختبارات الإحصائية التي تضمنها البحث، وهي اختبارات ت واختبارات تحليل التباين، ومعاملات ارتباط بيرسون، ومعاملات الانحدار، وتم استخلاص قيم أحجام العينات وقيم الدلالات الإحصائية والعملية لهذه الاختبارات من رسائل الماجستير التي تضمنتها عينة الدراسة. وبعد تحليل هذه البيانات خلصت الدراسة إلى مجموعة من النتائج أهمها: وجود علاقة إيجابية دالة إحصائيًّا بين الدلالة الإحصائية وحجم العينة في جميع الاختبارات الإحصائية، وعلاقة سلبية دالة إحصائيًّا بين حجم العينة ومستويات الدلالة العملية، لجميع الاختبارات الإحصائية عدا اختبارات معامل ارتباط بيرسون. وأوصت الدراسة بتضمين مؤشرات الدلالة العملية في مقررات الإحصاء ومناهج البحث لطلبة الدراسات العليا في الجامعات العمانية. ********************************************************************************* This study examined the effects of sample size on both the levels of statistical and practical significance in the statistical tests used in master’s theses in education at four Omani universities that offer master’s programs. The descriptive survey design was used to answer the research questions. A random sample of 628 master’s theses was selected for the analysis, representing 33.14% of the total population of 1,895 theses produced by the four universities. The researcher developed a content analysis tool to collect and analyze the data on the statistical tests spanning the use of t-test, analysis of variance tests, Pearson correlation, and regression analysis. The results revealed the presence of a statistically significant positive relationship between sample size and the statistical significance found in all the statistical tests, which means the bigger the sample, the greater the likelihood of finding a statistical significance. However, an inverse association was found between sample size and the levels of practical significance for all statistical tests, except in studies where Pearson correlation was used. The study recommends that indicators of practical significance be included in statistical and research methods courses for postgraduate students in Omani universities.